Parasites as possible cause of mass mortalities of the presently critically endangered clam Mesodesma mactroides on the Southwest Atlantic coast - Cremonte, Florencia (2004)
Specimens of Trichodina sp. were found on the gills of 58% of clams with moderate intensities without apparent cell damage. Coccidian were present in the nephridal tubules with both high prevalence (93%) and intensity of infection. Macrogamonts and meronts containing merozoites were the more frequently observed stages, obtruding the lumen of the nephridial tubules and associated with hypertrophying epithelial cells. Gregarines were observed inside the digestive epithelial cells and in the adjacent connective tissue in high intensities, with a prevalence of 64%. They were present alone or in groups of several individuals, in which case the epithelial cells were lysed. Turbellaria specimens were found inhabiting the lumen of the digestive tract, parasitising 30% of examined clams. Additionally, histological preparations from 36 dying clams from Monte Hermoso (40°32’S- 62°21’W, Buenos Aires province, Argentina, collected during mass mortality episode of November 1995) were re-examined. Despite the bad-condition of tissues, the same parasites found in Isla del Jabalí were observed, with the exception of gregarines: Trichodina sp. (100%), coccidians (100% from the five histological sections which included nephrida), turbellaria (14%). To support the hypothesis of a diseases-caused epidemic it is necessary to examine samples from other clam populations and to examine for virus infection.